A post-Keynesian view of central bank independence, policy targets, and the rules-versus-discretion debate - L. Randall Wray (Levy Economics Institute of Bard College, 2007)
This paper addresses three issues surrounding monetary policy formation: policy independence, choice of operating targets, and rules versus discretion. According to the New Monetary Consensus, the central bank needs policy independence to build credibility; the operating target is the overnight interbank lending rate, and the ultimate goal is price stability. This paper provides an alternative view, arguing that an effective central bank cannot be independent as conventionally defined, where effectiveness is indicated by ability to hit an overnight nominal interest rate target. Discretionary policy is rejected, as are conventional views of the central bank's ability to achieve traditional goals such as robust growth, low inflation, and high employment. Thus, the paper returns to Keynes's call for low interest rates and euthanasia of the rentier.
Keywords: E12; E31; E43; E52; E61; 330; Central Bank Independence; Interest Rate Determination; Real versus Nominal Rates; Interest Rate Targets; Rules versus Discretion